Directional Sweat Transport and Breathable Sandwiched Electrodes for Electrocardiogram Monitoring System. Issue 4 (16th December 2021) - Huang, Haizhou; Wu, Nan; Liu, Hui; Dong, Yide; Han, Longxiang; Wan, Shu; Dou, Guangbin; Sun, Litao
Abstract: Device–body interface is significant for acquiring high quality bio‐signals, preventing skin‐irritation, and minimizing the motion artifacts. However, low breathability of the typical substrate used in a flexible electronic device usually deteriorates the stability of device–body interface, which is imperative for long‐term application but commonly disregarded. In paper, a directional sweat transport and breathable electrode with three‐layer sandwiched structure is reported. The top hydrophilic hydrolyzed‐polyacrylonitrile (HPAN) layer and middle hydrophobic thermoplastic‐polyurethane (TPU) layer form Janus structure; and the bottom layer is an electrode layer of Ag nanowires (AgNWs). This dedicatedly designed electrode can transport sweat from skin to the top HPAN layer, while keeping low noise electrocardiogram (ECG) signal detection. In the trial of ECG monitoring, the results show that the electrode can achieve reliable recording with high signal noise rate (SNR) both in calm state (10.5 dB) and sweaty state (10.1 dB) with sweat tolerance. No allergy or obvious SNR degeneration is observed when utilizing the electrode owing to the effective sweat transport away from the device–body interface rather than accumulation. Finally, the application of the anti‐sweat accumulating electrode in wearable electronics is demonstrated. Abstract : Device–body interface is critical for reliable on‐skin sensing. Inspired by functional sportswear, a directional sweat transport and breathable sandwiched electrode is fabricated, which can achieve reliable electrocardiogram recording with high signal quality both in calm state and sweaty state. This demonstrates the potential applications of the structure to build diversified on‐skin electronics with sweat tolerance, breathability, and anti‐sweat accumulation.